Direction air supply design and optimization in industrial settings to reduce gaseous contaminant exposure. (15th May 2022) - Xu, Yukun; Cao, Changsheng; Ma, Mingyao; Jiao, Zheng; Cheng, Lingli; Xie, Wuhao; Gao, Jun; Zeng, Lingjie
Abstract: Ventilation systems designed for pollution removal in high-polluting workshops are usually ineffective due to the movement of workers. This work proposes a novel design method for direction air supply (DAS) system, which can protect personnel from exposure to gaseous contaminants during movement. A positioning system based on Kinect v2 for skeleton tracking is built in a confined test chamber. The 3D position of the head of personnel is identified and recorded by the positioning system, and the probability density of the residence time of personnel in each position of the chamber is counted. The target zone of DAS is determined by the proposed nonguarantee factor combined with the smallest enclosing circle algorithm. The sensitivity of the parameters of DAS to pollution removal at the height of the breathing zone is analyzed, and the findings reveal that increasing the size of the cylindrical nozzle is a more effective protective measure against gaseous contaminants than increasing the air supply velocity. The optimal solution of DAS for each target zone is screened, and the linear relationship between the diameter of the protected area and the radius of the cylindrical nozzle is fitted under a different protection factor. This work provides a design basis for reducing the respiratory exposure of personnel in high-polluting sites. Highlights: A design procedure for direction air supply (DAS) system is proposed. DAS system can protect respiratory health of personnel during movement. A positioning system based on Kinect v2 for skeleton tracking is built. Nozzle size is a sensitive parameter that affects pollution removal. Curves of the diameter of the protected area by DAS are fitted.